TSG-6 induces apoptosis of human hypertrophic scar fibroblasts via activation of the Fas/FasL signalling pathway - Li, X.-Y; Li, T; Li, X.-J; Wang, J.-N; Chen, Z (Folia biologica (Praha), 2018)
Tumour necrosis factor-stimulated gene 6 (TSG6) is a protective inflammatory reaction gene which is upregulated by inflammatory processes. Recent studies suggest that TSG-6 exhibits anti-scarring effects. However, the mechanism of TSG-6 action in the scar formation remains poorly understood. We investigated whether TSG-6 affects growth of the human hypertrophic scar fibroblasts (HSFs) via Fas/FasL signalling pathway. Cultured HSFs were transfected with a vector carrying the TSG6 gene (pLVX-Puro-TSG-6) or with a vector not containing the TSG6 gene (pLVX-Puro). Untransfected HSFs served as a control group to both transfected HSFs. The expressions level of TSG-6 was up-regulated in the pLVX-Puro-TSG-6 group at the protein and mRNA level. MTT and flow cytometry were used to assess the effect of TSG-6 on the growth and apoptotic status of HSFs. Finally, qRT-PCR and western blot were used to measure the expression levels of Fas, FasL, FADD, caspase-3 and caspase-8 in each group. The apoptosis rate was significantly enhanced and the growth rate reduced in the HSFs transfected with the TSG6 gene vector. The expression levels of Fas, FasL, FADD, caspase-3 and caspase- 8 were significantly raised in the TSG-6 overexpressing HSFs. It is concluded that increased expression of TSG-6 may induce apoptosis of human hypertrophic scar fibroblasts via activation of the Fas/FasL signalling pathway.
Keywords: Cell Adhesion Molecules; Fas Ligand Protein; Female; Adolescent; mužské pohlaví; Cell Survival; mladý dospělý; fas Receptor; Signal Transduction; Humans; jizva hypertrofická; dospělí; fibroblasty; lidé; apoptóza; viabilita buněk; RNA, Messenger; Fibroblasts; Gene Expression Regulation; ligand Fas; messenger RNA; ženské pohlaví; signální transdukce; Child; regulace genové exprese; Young Adult; molekuly buněčné adheze; dítě; Adult; Apoptosis; Male; mladiství; antigeny CD95; Cicatrix, Hypertrophic